Evaluation of adsorption-elution methods with positively and negatively charged membranes for virus concentration in municipal wastewater: New insight into effects of dissolved organic matter. Issue 3 (June 2022) - Wang, Zhen; Zhang, Chong-Miao; Li, Chen-Xin; Li, Yong-Fu; Mou, Xiao; You, Rui
Abstract: Efficient enrichment is the premise and guarantee for quantitative detection of pathogenic viruses in municipal wastewater. Some naturally occurring organic matter has an impact on the enrichment process because of interference with virus adsorption to the microporous membrane. In this study, the influence of dissolved organic matter (DOM) on the adsorption-elution method utilizing positively and negatively charged membranes for the recovery of bacteriophage MS2 in raw sewage and secondary effluent was investigated. For raw sewage and secondary effluent, the total recovery rate of virus with negatively charged membrane was 7.63% and 24.38% higher than that with positively charged membrane, respectively. Therefore, the adsorption-elution method with negatively charged membrane was suitable for raw sewage and secondary effluent. The recovery rate of elution step was lowest in all stages of adsorption-elution method, so the elution step was limiting step in the recovery of bacteriophage MS2 by adsorption-elution method. Fourier transform infrared spectroscopy (FTIR) with the fluorescence excitation-emission matrix spectroscopy (EEM) analysis revealed that tryptophan was dominant in the raw sewage, and humic acid (HA) was dominant in secondary effluent. Moreover, the surface roughness of the fouled membrane in the presence of tryptophan was higher than that of HA based on the morphology analysis by atomic force microscopy (AFM). According to X-ray photoelectron spectroscopy (XPS) analysis, the contribution of main functional groups in tryptophan and HA to the elution efficiency of bacteriophage MS2 was identified. In addition, the elution of bacteriophage MS2 was easy in the presence of tryptophan due to electrostatic force, and covalent bond / hydrogen bond in the presence of HA make bacteriophage MS2 difficult to be eluted. These findings can offer some evidence and scientific support for the standardization of enrichment methods in the water sample. Graphical Abstract: ga1 Highlights: The adsorption-elution method with NYM is suitable for municipal wastewater. The elution is limiting step in virus recovery by adsorption-elution method. The main DOM in raw sewage and secondary effluent would affect the elution of virus. Covalent bond/hydrogen bond mediated by HA makes elution of virus much harder.